54.8k views
22 votes
What is the result of subtracting the secound equation from the first -4x-2y=-2 x-2y=9

User Mobilpadde
by
5.0k points

1 Answer

9 votes

Answer:

When we subtract the second equation x-2y=9 from the first equation 4x-2y=-2, we get the value of x = 11/5.

Therefore, the required result is:

x = 11/5

Explanation:

Given

The first equation


-4x-2y=-2

The second equation


x-2y=9

Let us subtract the second equation from the first equation


-4x-2y=-2


-


\:\underline{x-2y=9}


-4x - 2y - (x - 2y) = -2 - 9


-4x -2y -x + 2y = -2-9


-5x = -11

divide both sides by -5


(-5x)/(-5)=(-11)/(-5)

Simplify


x=(11)/(5)

Thus, when we subtract the second equation x-2y=9 from the first equation 4x-2y=-2, we get the value of x = 11/5.

Therefore, the required result is:

x = 11/5

User AtinSkrita
by
4.8k points